The Role Of Relationship Between Relationship- Marketing And Banking Service Quality (Field Study In Syrian Commercial Banks In Lattakia Governorate) - عمار قصي; حلوم سنان; محمد بسام (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to determine the relationship of marketing with relationships, one of the marketing quality management strategies in its dimensions (shared value, commitment, trust, communication) and improving the quality of banking service in commercial banks in Lattakia Governorate. The researcher relied on the deductive approach, and relied on the descriptive approach to describe the research variables and analyze them based on the primary data that were collected. Banks to evaluate the quality of banking service from their point of view. The study reached results, including: The existence of a relationship between relationship marketing in all its dimensions with the quality of banking service All banks achieved levels of adoption above the average for all dimensions of relationship marketing, despite the existence of a discrepancy among them in that all banks achieved levels of quality above the average. , although there is a difference between them in it.